Design of tailor-made polymers with intrinsic micro-porosity for the “environmentally friendly” separation and storage of natural and industrial gas mixtures - El-mehalmey, Worood Adel (AUC Knowledge Fountain, 2015)
More than 80% of the worldwide commercial energy supply is based on fossil fuels. The heavy use of fossil fuels has resulted in large amounts of greenhouse gas emissions especially carbon dioxide (CO2) and depletion of the fossil fuel resources. Searching for alternative sources for energy such as hydrogen (H2) gas is a crucial step but requires excellent storage systems. Similarly, CO2 high level of production requires good capture and storage systems as well. Nanoporous polymers have found great application in the area of natural gas separation. Depending on the size and volume of the pores, the efficiency of the nanoporous polymers may vary. In as much, it is envisaged that these highly interesting polymers could also be used for capturing and storing CO2 and H2 gases for various applications. The high porosity in the micro and nano size scale rendered these polymers to possess massive surface area making these polymers remarkably suitable for capturing and storing various gases. In this study, a range of nanoporous polyimide polymers were synthesized using a two-step poly-condensation reactions of bis (carboxylic anhydride) with various aromatic diamines designed to investigate the effect of the polymeric microstructures on the conformational characteristics and consequently on the pore sizes and pore size distribution for gas storage application. The polymerization reactions resulted in various polymers of intrinsic micro-porosity (PIMs), which are known to comprise rigid backbone due to their lack of rotational freedom along the polymeric backbone and thus diminishing the ability of these chains to pack space efficiently and thus leading to the formation of intrinsic micro-pores. The polymers exhibited high surface area as determined by nitrogen adsorption and high thermal stability as determined by TGA. The high surface area was further validated using molecular simulation techniques. Structural modifications of the diamines have resulted into a variety of nanoporous polymeric structures. The chemical structures were confirmed using FTIR, NMR and GPC techniques. BET isotherms of the resultant polymers were carried out to evaluate their physical characteristics. The simulation results showed that the fractional free volume and the Connolly surface of the PIMs had greater values resulting from the nanoporosity of the rigid chains in agreement with the experimental findings and giving rise to a fundamental understanding of the influence of the polymeric structures on the ultimate intrinsic microporosity.